Adsorption kinetics of azinphosmethyl from aqueous solution onto pyrolyzed Horseshoe sea crab shell from the Atlantic Ocean - Gulen, J; Aroguz, AZ; Dalgin, D (ELSEVIER SCI LTD, 2005)
The adsorption behavior of azinphosmethyl on pyrolyzed Horseshoe Crab (Limulus polyphemus) outer shell, as a residue, from the Atlantic Ocean, collected along the Maine coast, USA, has been studied with regards to its kinetic and equilibrium conditions, taking into account adsorbate concentrations of 2 x 10(-3), 4 x 10(-3), 6 x 10-3, and 8 x 10-3, as well as temperatures of 30 degrees C, 40 degrees C, 50 degrees C, and 60 degrees C. The yield of adsorption of azinphosmethyl from aqueous solution ranged from 56.1% to 61% with temperature increasing. Kinetic studies showed that adsorption rate decreased as the initial azinphosmethyl concentration increased. It was found, that the adsorption reaction obeyed first-order kinetics. The overall rate constants were estimated for different temperatures. The activation energy for adsorption was about 1.52kJmol(-1), which implies that azinphosmethyl mainly adsorbed physically onto Horseshoe Crab outer shell. Langmuir and Freundlich isotherms were applied to the experimental data and isotherm constants were calculated. The thermodynamic parameters Delta G(0), Delta H-0 and Delta S-0 for the adsorption reaction were evaluated based on equilibrium data and in connection with this result the thermodynamic aspects of adsorption reaction were discussed. The adsorption was found to be endothermic in nature. The adsorbent used in this study proved highly efficient for the removal of azinphosmethyl. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: azinphosmethyl; adsorption kinetic; Freundlich isotherm; Langmuir isotherm; Horseshoe crab; shell; FLY-ASH; REMOVAL; PESTICIDES; BEHAVIOR; SORPTION; METHYL; WASTE; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels